Community readiness of urban farming practices in Malaysia - Mohamed Haris, Nur Bahiah; Yunus, Nur Amanina; Arif Shah, Jasmin (Human Resource Management Academic Research Society, 2022)
Urban farming refers to agriculture activities around cities with limited spaces. People can plant leafy or any easily grown vegetables at their home and urban space. Urban agriculture is not just a source of food but also a way forward of hedge against the negative effects of rapid urbanization. In fact, with the current situation of pandemic strike right now, it is an urgent need for communities to practice urban farming for their personal consumption, besides supporting food security, human safety, and a healthy lifestyle. Hence, this study will determine the community readiness of urban farming practices in Malaysia. Specifically, this study intends to determine the level of independent variables (knowledge, attitude and leadership) as well as community readiness, also the relationship between the factors towards community readiness in urban farming practices. This study was driven by Community Readiness Model (CRM) and employed a simple random sampling technique. A total of 353 participants from Peninsular Malaysia were sampled using a structured questionnaire through a google form. Data gathered was analysed using IBM SPSS (Version 26). The study revealed that the level of all independent variables and the community readiness are high. In addition, the three factors contribute significantly towards community readiness in urban farming practices. Hence, by reflecting to the aim of this study, the three factors (knowledge, attitude, and leadership) might lead to improve the readiness of the community towards urban farming activities in Malaysia. Thus, the finding has potentially to enhance the awareness and readiness of community either in urban or rural areas to involve in agriculture activities while promoting sustainable agriculture in the future.